Influence of Heat Treatment on Strain-induced Martensitic Transformation for Type-316 Stainless Steel - Nguyen, Thong Chung; Pham, Hang Thi; Nguyen, Hang Thi Nga (International Journal of Integrated Engineering, 2026)
Type 316 stainless steel, renowned for its excellent corrosion resistance and formability, undergoes strain-induced martensitic transformation during plastic deformation, which significantly alters its mechanical properties. Understanding the role of prior thermal treatments in modulating this transformation is crucial for optimizing performance in structural applications. In this study, the influence of prior thermal treatment on the strain-induced martensitic transformation in SUS316 stainless steel is investigated. The steel is subjected to various heat treatment processes, including water quenching and deep cryogenic treatment at -196 °C for duration of 6, 10 and 24 hours. Then, the effect of heat treatment and deep cryogenic treatment on the microstructure and the mechanical properties of the material is examined, taking into account phase transformations during plastic deformation. The obtained results show that the grain size of the austenite changes considerably after heat treatment. The cases without heat treatment indicate lower strength and ductility compared to the cases with heat treatment. Among investigated cases of thermal treatment, the specimen with heat-treated and cryogenic treatment during 24 hours exhibits the best strength and ductility. This result indicates that the combination of heat treatment and prolonged cryogenic treatment using liquid nitrogen produced the most effective improvement for this steel. This can be explained by the formation of a larger amount of martensite phase during tensile testing for specimen after combined heat and cryogenic treatment.